Kombinasi Pemberian Air Cucian Beras (Leri) dan Limbah Rebusan Tempe sebagai Pupuk Organik pada Tanaman Sawi - Basyar, Ahmad Syafiqul; Mei A, silvia Fitri (Program Studi Agroteknologi, 2022)
Mustard is an annual plant in the form of leaves, long trunks and fibrous roots. One of the organic materials that can be used for the cultivation of mustard plants is rice washing water and tempeh water boiled waste which contains many nutrients that plants need. The purpose of this study was to describe the effect of giving rice washing water and tempeh boiled waste on mustard plants and to find the right effect of the combination of the two. This research was conducted from November 1 to December 25, 2021 in Sumberrejo Village, Ambulu District, Jember Regency. This study used a 3 x 4 factorial pattern in a randomized block design (RAK) with 3 replications. The first factor, namely rice washing water, consisted of treatments A0 = 0 ml/l, A1 = 50 ml/l, A2 = 100 ml/l, A3 = 150 ml/l. And the second factor is tempeh boiled waste consisting of L1 = 20 ml/l, L2 = 40 ml/l, L3 = 60 ml/l. The collected data was analyzed by means of variance (Anova), if it was significantly different, it was followed by Duncan's 5% test. The parameters of root length and plant wet weight showed significantly different results and very significant differences.